The potential of cultural and chemical control practices for enhancing productivity of banana ratoons - Kagoda, F.; Rubaihayo, P.R.; Tenywa, M.M. (2005)
A study of the effect of plant population, fertiliser application, number of suckers retained per stool and desuckering time on the 5th and 6th banana ratoons was conducted on Kibuzi (AAA-EA) plantation from October 2000 to December 2002. The plantation had earlier (October 1999 to October 2000) received poor management which resulted in high infestation by weevils and nematodes, small bunches and low yields. The study was accomplished in two experiments. In the first experiment, the original spacings of 2.5x2.5m (1,600 plants ha-1), 3x3m (1,111 plants ha-1) and 3.75x3.75m (711 plants ha-1) were maintained in main plots when the plantation was redesigned into a split plot experiment for each original plot with the sub-plots containing N/K fertilisers applied at the rates of 0/0, 50/100 and 100/200-kg ha-1 yr-1 in two splits since these nutrients were limiting. Phosphorus was applied as a blanket cover at 75 kg P ha-1 yr-1. Three suckers were maintained per stool and extra suckers removed using a hand hoe giving a population of 4800, 3,333 and 2133 plants ha-1 at 2.5x2.5m, 3x3m and 3.75x3.75m, respectively. The second experiment originally at a spacing of 3x3 m had a split plot design with 2 and 3 suckers per stool maintained in the main plots and extra suckers removed at time intervals of 1 month, 2 months and 3 months in the sub-plots. Curaterr 5G (carbofuran) and Agro-chlordi (chlorpyrifos/dimethoate mixture) were applied in all the sub-plots at the beginning of both experiments (Oct. 2000) to control banana weevils and nematodes.Results of effect of plant population and fertiliser application showed that in the 5th ratoon, plant population had no significant influence on growth characters of flowering plants but flowering to harvesting duration and yield ha-1 significantly (P < 0.05) decreased with decrease in plant population. The 6th ratoon had a significant (P < 0.05) decrease in growth characters of plant height, flowering to harvesting duration, and a significant (P < 0.05) increase in yield components of hands per bunch and finger girth with decrease in plant population. Despite fertiliser application at N50K100 and N100K200, there was a remarkable decline in the 6th ratoon due to toppling and snapping following windy weather. Results of number of suckers retained per stool and desuckering time indicated higher growth parameters in the 5th than the 6th ratoon due to population reduction owing to high mat, weevil and nematode infected plants being vulnerable to wind damage. Unlike the 5th ratoon, the 6th ratoon had significant (P < 0.05) decrease in all growth parameters with increase in desuckering time. Better economic benefits were observed from early desuckering and N50K100 treatments in both ratoons. Although curaterr 5G significantly (P < 0.05) reduced nematode populations resulting in reduced necrosis index and agro-chlordi insecticide treatment following curaterr 5G treatment effectively eliminated weevils from the ratoons, the plants could not effectively recover their rooting system since the corms had been damaged beyond recovery. Thus, were infestation of banana weevils and nematodes is apparent, it is critical to initiate application of control interventions before the 5th ratoon. Besides, results of the study indicate that its better to establish new plantations rather making efforts to rehabilitate long neglected plantations.